Trends in mortality and in the number of people infected with HIV/AIDS in Peru, 2000-2021: an ecological study using joinpoint regression analysis - Quiroz-Ruiz, Hans Ramón (2023)
Introduction: Mortality from HIV/AIDS is one of the main indicators to monitor this public health problem. Objective: Analyze the changes in the trend in mortality and in the number of people infected with HIV/AIDS in Peru 2000-2021. Material and Methods: Ecological study based on open data on people living with HIV/AIDS in the period 2000-2021. Mortality rates were obtained from the Single National Health Information Repository. Data on new cases of HIV/AIDS were obtained from CDC Peru sources. A joinpoint regression analysis estimated trends using mean percentage change (APC); considering sex, life stages and regions, p values ​​less than 0.05 being significant. Results: The general mortality trend had no significant changes (APC=-1.3 [95% CI: -2.6; 0.1]); nine regions presented increasing mortality trends; mortality in women decreased (APC=-2.2 [95% CI: -3.7; -0.6]); an increasing trend was observed in adolescent mortality (APC=6.3 [95% CI: 2.3; 10.3]). An increasing trend was demonstrated in the number of people infected with HIV (APC=3.73 [95% CI: 2.6; 4.8]) and the trend of AIDS cases decreased from 2004 (APC=-2.54 [95% CI: -4.3; -0.7]). Conclusion: It was found that there are increasing trends in mortality from HIV/AIDS in adolescents and in a significant number of regions of the Peruvian highlands, being a key priority to deepen the management and approach of these populations.